Navigation in multiobjective optimization methods. Issue 1 (23rd November 2016) - Allmendinger, Richard; Ehrgott, Matthias; Gandibleux, Xavier; Geiger, Martin Josef; Klamroth, Kathrin; Luque, Mariano
Abstract: Building on previous work of the authors, this paper formally defines and reviews the first approach, referred to as navigation, towards a common understanding of search and decision‐making strategies to identify the most preferred solution among the Pareto set for a multiobjective optimization problem. In navigation methods, the decision maker interactively learns about the problem, whereas the decision support system learns about the preferences of the decision maker. This work introduces a detailed view on navigation leading to the identification of integral components and features. A number of different existing navigation methods are reviewed and characterized. Finally, an overview of applications involving navigation is given, and promising future research direction are discussed.